A Neutraceutical by Design: The Clinical Application of Curcumin in Colonic Inflammation and Cancer. (6th November 2012) - Soni, D.; Salh, B.
Abstract : Unquestionably, the natural food additive curcumin, derived from the colorful spice turmeric used in many Asian cuisines, possesses a diverse array of biological activities. These range from its anti-inflammatory, antineoplastic, and metabolic modifying properties to surprising roles in disorders ranging from Alzheimer's disease to cystic fibrosis. Its effects on growth factor receptors, signaling molecules, and transcription factors, together with its epigenetic effects are widely considered to be extraordinary. These pleiotropic attributes, coupled with its safety even when used orally at well over 10 g/day, are unparalleled amongst pharmacological agents. However, there is one drawback; apart from the luminal gastrointestinal tract where its pharmacology predicts that reasonable drug levels can be attained, its broader use is hampered by its poor solubility and hence near undetectable plasma levels. Medicinal chemistry and nanotechnology have resulted in the generation of compounds where the modified drug or its delivery system has improved matters such that this shortcoming has been addressed to some extent, with the surprising finding that it remains safe to use. It is predicted that either the parental compound or its derivatives may eventually find a place in the therapeutic management protocols of several conditions.